THE ROLE OF WAQF MANAGEMENT IN THE ESTABLISHMENT OF SOCIAL WELFARE: A CASE STUDY OF YOBE ISLAMIC CENTRE, NIGERIA - Hassan, Hadiza; Ibrahim, Sheriff Muhammad (International Journal of Sukuk and Waqf Research, 2022)
Waqf is one of the factors for economic prosperity in Islamic civilization established by the Qur'an and Sunnah and has been practiced by Muslim generations as a financial charitable act established by withholding immovable and movable properties to perpetually spend its revenue to fulfill public or family needs, based on the preferences and conditions set by the founder. The institution of Waqf has been an effective way of reducing and eradicating poverty among Muslim communities. Yobe state government established the zakat and waqf management department under the Ministry of religious affairs (MORA) following the declaration of the Shariah system in the state on the 23rd of October 2002 to manage all activities related to zakat and Waqf. The aims and objectives of the institution are to promote the social welfare of the communities and to promote the socio-economic status of Muslims. Yobe state government engaged in establishing one of the most notable waqf investments in the state to promote charitable activities and encourage the Muslim community to continue investing in institutional waqf. However, despite establishing the institution, very few institutionalized waqf practices could be traced in the state. Thus, this research aims to examine the problems affecting the institution of waqf in Yobe State and recommends solutions to address the identified problems. The study applied qualitative research methods by using interviews and literature reviews to examine the major challenges facing the institution of Waqf and Zakat in Damaturu.JEL Classification Codes: B55, I39, Q15, O35.